Early medieval architecture - Stalley, R. A; Oxford University Press (Oxford ; New York : Oxford University Press, 1999)
"Departing from the traditional emphasis on chronological development, the book is structured thematically to enable key issues to be thoroughly examined. Chapters cover patronage, the cult of saints, the language of the Romanesque, the engineering achievements of the builders, and the symbolic meanings of architecture. The extreme richness and variety of European architecture is explored in terms of the social and religious aspirations of the time."--Jacket
-- The Christian basilica -- The Carolingian Renaissance: the basilica transformed -- Symbolic architecture -- Secular architecture in the age of feudalism -- Patron and builder -- Art and engineering -- Architecture and pilgrimage -- Architecture and monasticism -- The language of architecture -- Diversity in the Romanesque Era -- Epilogue: The shadow of Rome
Includes bibliographical references and index
Keywords: Architecture, Medieval -- Europe; Church architecture -- Europe